2020
DOI: 10.3390/jcm9020596
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Forecasts of the COVID-19 Epidemic in Guangdong and Zhejiang, China: February 13–23, 2020

Abstract: The ongoing COVID-19 epidemic continues to spread within and outside of China, despite several social distancing measures implemented by the Chinese government. Limited epidemiological data are available, and recent changes in case definition and reporting further complicate our understanding of the impact of the epidemic, particularly in the epidemic's epicenter.Here we use previously validated phenomenological models to generate short-term forecasts of cumulative reported cases in Guangdong and Zhejiang, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
202
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(209 citation statements)
references
References 18 publications
0
202
0
7
Order By: Relevance
“…It is used in microbiological research, diagnostics and in the production of antiviral vaccines-all situations that require knowledge of the amount of virus being analyzed or used. We used tissue-culture infectious dose (TCID) per milliliter for COVID-19 persistence evaluation [15][16][17][18][19].…”
Section: Rationalementioning
confidence: 99%
“…It is used in microbiological research, diagnostics and in the production of antiviral vaccines-all situations that require knowledge of the amount of virus being analyzed or used. We used tissue-culture infectious dose (TCID) per milliliter for COVID-19 persistence evaluation [15][16][17][18][19].…”
Section: Rationalementioning
confidence: 99%
“…If we determine the peak of the outbreak from the 5 days moving average of the incidence curve, then there are 15 provinces taking 7-11 days from their first case to their peak, 9 provinces taking 12-15 days, and 6 provinces taking more than 15 days. If we define the end of the outbreak as the day when the 5 days moving average of the growth rate becomes smaller than 1%, then 7 provinces spent 8-12 days from the peak to the end, 7 provinces spent 13-16 days, 13 provinces spent 17-20 days, and 2 provinces spent 21-22 days. For the six provinces that have the longest duration from the start of their outbreak to the peak (more than 15 days), it took 8-13…”
Section: Quantification Of the Initial Reactions And Ramping Up Of Comentioning
confidence: 99%
“…Also the authors determined the number of cases with the epidemic growth model Fan et al [19]. Roosa et al (2020) analyzed the number of cases in some regions in China with generalized logistic growth model (GLM), Richards Model and Sub-Epidemic Model in a short-term (10 days). They found that the number of cases will increase.…”
Section: Discussionmentioning
confidence: 99%